Pengendalian Kualitas Produksi Air Minum Dalam Kemasan Menggunakan Peta Kendali - Halifatunnisa, Nur; Baskara, Zulhan Widya; Harsyiah, Lisa; Zulhan Widya Baskara (Program Studi Matematika, 2024)
The most popular drinking water product produced by PT.X is the 220 ml glass packaging product. This product experienced the most production defects at 0.086% of total production. Based on observations that have been made, there are several problems that cause defective products, such as damaged packaging and poor water quality. So PT.X in maintaining production quality must improve the process of maintaining quality control. The aim of this research is in line with the problems faced by PT.X, namely controlling the quality of bottled drinking water using a decision on belief control chart. Control charts are used to monitor whether product defect data is statistically controlled or not. One of the control charts used to monitor whether product defect data is statistically controlled or not is the Decision on Belief control chart, because the Decision on Belief control chart is more sensitive to data shifts so that faster in detecting data that goes outside control limits or is out of control. Based on the graph of the results of the decision on belief control chart, of the 25 data there are 24 data that are out of the upper control limit and the lower control limit, meaning that the decision on belief control chart is sensitive to data shifts in detecting out of control data. Based on the results of the average run length calculation, it is concluded that the decision on belief control chart is weak in detecting out of control data because the shift value obtained is getting bigger.